A pellet binder and its preparation method and application

By using a pellet binder prepared in combination with zinc-containing carboxyl complex slurry, the problems of large amount of traditional binder added, high cost and easy fracturing are solved, and the effects of low addition amount, high cohesion strength and transportation stability are achieved.

CN115652084BActive Publication Date: 2025-04-18JIANGSU SAIFURUI NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211341324.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2025-04-18
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

Traditional pellet binder is added in large amount, high cost and easy to break, making it difficult to meet the stability requirements of phosphorus tailing pellets during transportation.

Method used

The pellet binder is prepared by drying and grinding steps to form a high viscosity liquid to reduce the addition amount and increase the cohesive strength of the pellet.

Benefits of technology

The advantages of low addition of pellet binder, high pellet forming rate, high cohesive strength, cold press free fall height of more than 3 meters and high temperature explosion-proof are achieved, which significantly improves the transportation stability of phosphorus tailing pellets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003916409830000071
    Figure BDA0003916409830000071
  • Figure BDA0003916409830000081
    Figure BDA0003916409830000081
  • Figure BDA0003916409830000082
    Figure BDA0003916409830000082
Patent Text Reader

Abstract

The present invention provides a pellet binder and a preparation method and application thereof, belonging to the technical field of non-metallic mineral metallurgy. In the zinc-containing carboxyl complex slurry of the present invention, carboxymethyl cellulose ester and sodium polyacrylate can be interlaced and complexed, and the viscosity-enhancing effect of the formed composite slurry is significantly higher than that of traditional carboxymethyl cellulose; the added amphoteric metal compound reacts chemically with the acidic components in the phosphate tailings to form complex particles, improve the cohesive energy of the pellets, and give them a higher chemical bonding strength; the added inorganic gel particles and modified montmorillonite as inorganic adhesives cooperate with the composite organic binder (carboxymethyl cellulose ester and sodium polyacrylate), which can give the phosphate tailings pellets an extremely high pelletizing rate and cohesive energy, thereby avoiding fragmentation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-metallic mineral metallurgy, and in particular to a pelletizing binder and a preparation method and application thereof. Background Art

[0002] As an important non-renewable resource, phosphate rock is widely used in medicine, food, fuel, chemical industry, national defense and new energy fields. Especially in recent years, with the rapid development of new energy vehicles, as an important raw material for lithium iron phosphate of power batteries, its price has been rising steadily. Especially under the establishment of a total control system for the mining of important phosphate mines, the mining quota allocated to each mining enterprise is quantitatively controlled. The recycling and reuse of powdered phosphate tailings (diameter <10mm) that were previously treated as waste has become of great commercial value.

[0003] At present, the effective utilization method for phosphorus tailings powder in the industry is to use a binder to form a sphere, and then put it into a furnace for sintering, giving it enough strength, and maintaining a stable shape during pellet production, transportation, and transportation. At present, the pellet binders used more in the industry are mainly bentonite and organic binders. The bentonite binder technology is relatively mature, and its advantage is low cost, but the addition amount is often more than 2wt%, which will seriously reduce the phosphorus content quality of the phosphorus tailings pellets and increase energy consumption. The amount of organic binder is significantly lower than bentonite, but its price is high, and it is currently immature in the treatment of phosphorus tailings powder. The pellets made are insufficient in cohesion, low in strength, and easy to break again during transportation. Summary of the invention

[0004] The object of the present invention is to provide a pellet binder and a preparation method and application thereof, which can solve the problems of large addition amount, high cost and easy breakage of traditional pellet binders.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a pelletizing binder, which comprises the following raw materials by weight:

[0007] 40-60 parts of zinc carboxyl complex slurry, 20-30 parts of inorganic gel particles, 10-20 parts of amphoteric metal compounds, and 5-15 parts of modified montmorillonite;

[0008] The raw materials for preparing the zinc-containing carboxyl complex slurry include: 20 parts of carboxymethyl cellulose ester, 10 parts of sodium polyacrylate, 5 parts of sodium lignin sulfonate, 1 part of coupling agent, 1 part of sodium hydroxide, 20 parts of water and 3 parts of zinc compound.

[0009] Preferably, the preparation method of the zinc-carboxyl complex slurry comprises:

[0010] Mixing carboxymethyl cellulose ester, sodium polyacrylate, sodium lignin sulfonate and a coupling agent to obtain a mixed powder;

[0011] After dissolving sodium hydroxide in water, the obtained sodium hydroxide solution, mixed powder and zinc compound are mixed to obtain zinc-containing carboxyl complex slurry.

[0012] Preferably, the carboxymethyl cellulose ester is one or more of carboxymethyl cellulose acetate propionate, carboxymethyl cellulose acetate butyrate and carboxymethyl cellulose stearate.

[0013] Preferably, the coupling agent is one or more of KH550, KH560, KH570, tetrabutyl titanate, isopropyl trititanate and aluminate coupling agents.

[0014] Preferably, the zinc compound is one or more of zinc oxide, zinc chloride, zinc sulfate, zinc acetate and zinc hydroxide.

[0015] Preferably, the inorganic gel particles are one or more of calcium oxide, cement, high modulus sodium silicate, magnesium chloride, alum and hydrotalcite.

[0016] Preferably, the amphoteric metal compound is one or more of aluminum oxide, aluminum hydroxide, iron oxide and cobalt oxide.

[0017] Preferably, the modified montmorillonite is sodium montmorillonite and / or cellulose ether modified montmorillonite.

[0018] The present invention provides a method for preparing the pellet binder according to the above technical solution, comprising the following steps:

[0019] The zinc-containing carboxyl complex slurry, inorganic gel particles, amphoteric metal compounds and modified montmorillonite are mixed, and then dried and ground in sequence to obtain a pellet binder.

[0020] The present invention provides application of the pellet binder described in the above technical solution or the pellet binder prepared by the preparation method described in the above technical solution in phosphate tailings powder.

[0021] The invention provides a pellet binder, which comprises the following raw materials, measured by weight: 40 to 60 parts of zinc-containing carboxyl complex slurry, 20 to 30 parts of inorganic gel particles, 10 to 20 parts of amphoteric metal compounds, and 5 to 15 parts of modified montmorillonite; the raw materials for preparing the zinc-containing carboxyl complex slurry include: 20 parts of carboxymethyl cellulose ester, 10 parts of sodium polyacrylate, 5 parts of sodium lignin sulfonate, 1 part of coupling agent, 1 part of sodium hydroxide, 20 parts of water and 3 parts of zinc compound. In the zinc-containing carboxyl complex slurry of the present invention, carboxymethyl cellulose ester and sodium polyacrylate can be interlaced and complexed, and the viscosity-increasing effect of the formed composite slurry is significantly higher than that of traditional carboxymethyl cellulose; the amphoteric metal compound reacts chemically with the acidic components (phosphate groups) in the phosphate tailings to form complex particles, thereby improving the cohesive energy of the pellets and giving them higher chemical bonding strength; the inorganic gel particles and modified montmorillonite as inorganic adhesives cooperate with the composite organic binder (carboxymethyl cellulose ester and sodium polyacrylate) to give the phosphate tailings pellets extremely high pelletization rate and cohesive energy, thereby avoiding fragmentation; sodium wood sulfonate acts as a promoter to promote the bonding of the inorganic gel particles.

[0022] In the pellet binder provided by the present invention, natural carboxymethyl cellulose ester and organic sodium polyacrylate used in zinc-containing carboxyl complex slurry are chemically complexed with zinc compounds under alkaline conditions provided by sodium hydroxide to form a stable organic binder complex slurry. During the water absorption process of the complex, smaller molecular weight sodium polyacrylate can be dispersed and penetrated into larger molecular weight carboxymethyl cellulose ester, greatly improving the water absorption expansion rate of carboxymethyl cellulose ester to form a high-viscosity liquid, thereby reducing the added amount of the pellet binder; at the same added amount, the viscosity of the high-viscosity liquid is 15 to 20 times that of hydroxymethyl cellulose, which is significantly better than existing binder products.

[0023] The pellet binder provided by the present invention has the advantages of low addition amount (0.5wt%), high pellet forming rate, high cohesive strength, cold-pressed free fall height exceeding 3 meters and high-temperature explosion resistance. The results of the embodiment show that after the pellet binder of the present invention is used for curing phosphate tailings powder, it can be dropped 5 times at 3 meters without breaking.

[0024] The pellet binder formed by the organic-inorganic bonding compound of the present invention has the advantages of low cost, convenient use, low burning residue and low addition amount without affecting the quality of phosphate rock. DETAILED DESCRIPTION

[0025] The present invention provides a pelletizing binder, which comprises the following raw materials by weight:

[0026] 40-60 parts of zinc carboxyl complex slurry, 20-30 parts of inorganic gel particles, 10-20 parts of amphoteric metal compounds, and 5-15 parts of modified montmorillonite;

[0027] The raw materials for preparing the zinc-containing carboxyl complex slurry include: 20 parts of carboxymethyl cellulose ester, 10 parts of sodium polyacrylate, 5 parts of sodium lignin sulfonate, 1 part of coupling agent, 1 part of sodium hydroxide, 20 parts of water and 3 parts of zinc compound.

[0028] In the present invention, unless otherwise specified, the required raw materials are all commercially available products well known to those skilled in the art or can be prepared according to well-known methods.

[0029] The pellet binder provided by the present invention comprises 40 to 60 parts by mass, preferably 45 to 50 parts by mass of zinc-carboxyl complex slurry.

[0030] In the present invention, the raw materials for preparing the zinc-containing carboxyl complex slurry include: 20 parts of carboxymethyl cellulose ester, 10 parts of sodium polyacrylate, 5 parts of sodium lignin sulfonate, 1 part of coupling agent, 1 part of sodium hydroxide, 20 parts of water and 3 parts of zinc compound.

[0031] In the present invention, the carboxymethyl cellulose ester is preferably one or more of carboxymethyl cellulose acetate propionate, carboxymethyl cellulose acetate butyrate and carboxymethyl cellulose stearate; when the carboxymethyl cellulose ester is two or more of the above, the present invention has no special restrictions on the ratio of different types of carboxymethyl cellulose esters, and any ratio is acceptable. The present invention uses carboxymethyl cellulose ester as an organic binder component.

[0032] In the present invention, the coupling agent is preferably one or more of KH550, KH560, KH570, tetrabutyl titanate, isopropyl trititanate and aluminate coupling agent. When the coupling agent is two or more of the above, the present invention has no special restrictions on the ratio of different types of coupling agents, and any ratio is acceptable. The present invention utilizes the reaction of the coupling agent with the inorganic gel particles to improve the bonding performance between the organic matter and the phosphate tailing particles.

[0033] The invention uses sodium polyacrylate for thickening and forms a complex with carboxymethyl cellulose ester to increase the viscosity of the pellet binder; the role of sodium lignin sulfonate is to improve the bonding force between the phosphorus tailings and the organic binder (carboxymethyl cellulose ester and sodium polyacrylate); the role of sodium hydroxide is to provide an alkaline environment.

[0034] In the present invention, the zinc compound is preferably one or more of zinc oxide, zinc chloride, zinc sulfate, zinc acetate and zinc hydroxide; when the zinc compound is two or more of the above, the present invention has no special limitation on the ratio of different types of zinc compounds, and any ratio is acceptable. The present invention utilizes zinc compounds to complex with carboxymethyl cellulose ester and organic sodium polyacrylate to increase viscosity.

[0035] In the present invention, the method for preparing the zinc-containing carboxyl complex slurry preferably comprises:

[0036] Mixing carboxymethyl cellulose ester, sodium polyacrylate, sodium lignin sulfonate and a coupling agent to obtain a mixed powder;

[0037] After dissolving sodium hydroxide in water, the obtained sodium hydroxide solution, mixed powder and zinc compound are mixed to obtain zinc-containing carboxyl complex slurry.

[0038] The present invention has no special limitation on the process of mixing the carboxymethyl cellulose ester, sodium polyacrylate, sodium lignin sulfonate and coupling agent, and the materials can be uniformly mixed according to the process well known in the art.

[0039] In the present invention, after mixing the sodium hydroxide solution with the mixed powder, the zinc compound is added to the obtained slurry, heated to 80° C., and stirred for 2 hours. The present invention has no particular limitation on the stirring rate, and the materials can be mixed uniformly according to a process well known in the art.

[0040] Based on the mass fraction of the zinc-carboxyl complex slurry, the pellet binder provided by the present invention includes 20 to 30 parts of inorganic gel particles, preferably 25 parts.

[0041] In the present invention, the inorganic gel particles are preferably one or more of calcium oxide, cement, high modulus sodium silicate, magnesium chloride, alum and hydrotalcite; the cement is preferably PO32.5; the modulus of the high modulus sodium silicate is preferably 1.5-3; when the inorganic gel particles are two or more of the above, the present invention has no special restrictions on different types of inorganic gel particles, and any ratio is acceptable. The present invention uses inorganic gel particles as inorganic adhesives.

[0042] Based on the mass fraction of the zinc-containing carboxyl complex slurry, the pellet binder provided by the present invention includes 10 to 20 parts of amphoteric metal compounds, preferably 12 to 16 parts. In the present invention, the amphoteric metal compound is preferably one or more of aluminum oxide, aluminum hydroxide, iron oxide and cobalt oxide; when the amphoteric technical compound is two or more of the above, the present invention has no special restrictions on different types of amphoteric metal compounds, and any ratio is acceptable. The present invention utilizes amphoteric metal compounds to react with acidic components in phosphate tailings to improve chemical bonding strength.

[0043] Based on the mass fraction of the zinc-containing carboxyl complex slurry, the pellet binder provided by the present invention comprises 5 to 15 parts of modified montmorillonite, preferably 9 to 13 parts. The present invention utilizes modified montmorillonite as an inorganic adhesive.

[0044] In the present invention, the modified montmorillonite is preferably sodium montmorillonite and / or cellulose ether modified montmorillonite; the cellulose ether is preferably carboxymethyl cellulose. When the modified montmorillonite is sodium montmorillonite and cellulose ether modified montmorillonite, the present invention has no special limitation on the ratio of the two, and any ratio is acceptable.

[0045] The present invention has no particular limitation on the source of the sodium-based montmorillonite and / or cellulose ether-modified montmorillonite, and any commercially available product known in the art may be used. In the embodiment of the present invention, the sodium-based montmorillonite and cellulose ether-modified montmorillonite are purchased from Chaoyang Jiasheng Mineral New Materials Co., Ltd.

[0046] The present invention provides a method for preparing the pellet binder according to the above technical solution, comprising the following steps:

[0047] The zinc-containing carboxyl complex slurry, inorganic gel particles, amphoteric metal compounds and modified montmorillonite are mixed, and then dried and ground in sequence to obtain a pellet binder.

[0048] The present invention preferably stirs the zinc-carboxyl complex slurry, inorganic gel particles, amphoteric metal compounds and modified montmorillonite, and then mixes them evenly in a mixer; the present invention has no special restrictions on the stirring rate and time, and the materials can be stirred evenly according to the process well known in the art.

[0049] In the present invention, the drying temperature is preferably 50-80° C.; the drying is preferably carried out in an oven; the present invention has no special restrictions on the drying time and the grinding process, and can be carried out according to the process known in the art. In the embodiment of the present invention, a steel grinder is used to grind the powder.

[0050] The present invention provides the application of the pellet binder described in the above technical solution or the pellet binder prepared by the preparation method described in the above technical solution in phosphate tailings powder. The present invention has no special limitation on the method of the application, and it can be applied according to the method well known in the art. In an embodiment of the present invention, specifically, a pellet binder is added to the phosphate tailings powder (water content 15wt%), mixed evenly, stirred, poured into a pelletizing device, extruded and molded, and cured for 7 days to obtain phosphate tailings pellets. In the present invention, the mass proportion of the pellet binder in the phosphate tailings powder is preferably 0.5%. The present invention has no special limitation on the pelletizing device and extrusion molding, and it can be carried out according to the well-known process using the corresponding equipment well known in the art.

[0051] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] In the following examples, the modulus of high modulus sodium silicate is 1.5-3; sodium montmorillonite and cellulose ether modified montmorillonite are purchased from Chaoyang Jiasheng Mineral New Materials Co., Ltd.; carboxymethyl cellulose acetate propionate is purchased from Chongqing Lihong Fine Chemical Co., Ltd.; carboxymethyl cellulose acetate butyrate is purchased from Eastman Company of the United States.

[0053] Example 1

[0054] Weigh 20g of carboxymethyl cellulose acetate propionate, 10g of sodium polyacrylate, 5 parts of sodium lignin sulfonate and 1 part of tetrabutyl titanate and mix them evenly to obtain a mixed powder; weigh 1g of sodium hydroxide and dissolve it in 20g of water. After it is completely dissolved, pour the mixed powder into it and stir and mix evenly to obtain a slurry; weigh 3 parts of zinc oxide and put it into the slurry, heat it in a water bath to 80°C, stir for 2h, and obtain a zinc-containing carboxyl complex slurry;

[0055] Weigh 50 g of the above-mentioned zinc-containing carboxyl complex slurry, add 25 g of high modulus sodium silicate, 16 g of aluminum oxide and 9 g of carboxymethyl cellulose modified montmorillonite, stir, and mix evenly with a mixer, spread the mixed raw materials on a tray, dry them in an oven at 80°C, and grind them into powder with a steel grinder to obtain a pellet binder.

[0056] Example 2

[0057] Weigh 20g of carboxymethyl cellulose acetate butyrate, 10g of sodium polyacrylate, 5 parts of sodium lignin sulfonate and 1 part of silane coupling agent KH570, mix them evenly to obtain a mixed powder; weigh 1g of sodium hydroxide and dissolve it in 20g of water, after it is completely dissolved, pour the above mixed powder into it, stir and mix evenly to obtain a slurry; weigh 3g of zinc acetate, add it to the above slurry, heat it in a water bath to 80°C, stir for 2h, and obtain a zinc-containing carboxyl complex slurry;

[0058] Weigh 45 g of the above-mentioned zinc-carboxyl complex slurry, add 25 g of cement (PO32.5), 5 g of calcium oxide, 12 g of aluminum hydroxide and 13 g of sodium montmorillonite, stir, and mix evenly with a mixer. Spread the mixed raw materials on a tray, dry them in an oven at 80°C, and grind them into powder with a steel grinder to obtain a pellet binder.

[0059] Application Example 1

[0060] 0.5% by weight of the pelletizing binder prepared in Example 1 was added to the phosphate tailings powder (water content 15wt%), mixed evenly, stirred, poured into a pelletizing device, extruded and cured for 7 days to obtain phosphate tailings pellets.

[0061] Application Example 2

[0062] 0.5% by weight of the pelletizing binder prepared in Example 2 was added to the phosphate tailings powder (water content 15wt%), mixed evenly, stirred, poured into a pelletizing device, extruded and cured for 7 days to obtain phosphate tailings pellets.

[0063] Comparative application example 1

[0064] Traditional montmorillonite is used as a pelletizing binder: 3% by weight of sodium-based montmorillonite is added to the phosphate tailings powder (water content 15wt%), mixed evenly, stirred, poured into the pelletizing equipment, extruded and cured for 7 days to obtain phosphate tailings pellets.

[0065] Comparative Application Example 2

[0066] Carboxymethyl cellulose is used as a pellet binder: 0.5% by weight of carboxymethyl cellulose is added to phosphate tailings powder (water content 15wt%), mixed evenly, stirred, poured into a pelletizing device, extruded and cured for 7 days to obtain phosphate tailings pellets.

[0067] Performance Testing

[0068] 1) The compressive strength of the phosphate tailings pellets prepared in Application Examples 1-2 and Comparative Application Examples 1-2 was tested by the 7-day unconfined compressive strength method. Three parallel samples were made for each case, which were recorded as Sample 1, Sample 2 and Sample 3 respectively. The results are shown in Table 1.

[0069] Table 1 Compressive strength of phosphate tailings pellets prepared in Application Examples 1-2 and Comparative Application Examples 1-2

[0070]

[0071]

[0072] It can be seen from Table 1 that the phosphate tailings pellets prepared with the pellet binder provided by the present invention have a 7-day unconfined compressive strength of more than 3 MPa, which is significantly higher than the 2.2 MPa of the traditional pelletizing agent montmorillonite and 1.88 MPa of the organic binder, and the prepared phosphate tailings pellets have excellent cohesive strength.

[0073] 2) The impact resistance was tested by a drop test: the phosphate tailings pellets cured for 7 days in Application Examples 1-2 and Comparative Application Examples 1-2 were dropped from a specified height onto a 10 mm thick steel plate to observe their fragmentation. Three parallel samples were made for each case, which were recorded as Sample 1, Sample 2 and Sample 3 respectively. The results are shown in Table 2.

[0074] Table 2 Crushing of phosphate tailings pellets prepared in Application Examples 1-2 and Comparative Application Examples 1-2

[0075]

[0076] As can be seen from Table 2, the pellet binder provided by the present invention has an excellent impact resistance effect on powdered phosphate tailings, which can basically remain intact after falling three times at a height of 3 meters, and can better solve the problem of breakage of phosphate pellets during transportation.

[0077] 3) The pellet forming rate was tested by comparing the ratio of pellets to crushed powder: 200 kg of phosphorus tailings powder was taken and mixed evenly according to the methods of Application Examples 1-2 and Comparative Application Examples 1-2, respectively, and pressed into shape by a pelletizing machine once, and pellets with a diameter of more than 20 mm were collected and weighed, recorded as M1, and the one-time forming rate W was calculated, and the formula was:

[0078]

[0079] The results are shown in Table 3.

[0080] Table 3 One-time forming rate of phosphate tailings pellets prepared in application examples 1 to 2 and comparative application examples 1 to 2

[0081] project Application Example 1 Application Example 2 Comparative application example 1 Comparative Application Example 2 One-time group request rate 91.2% 88.6% 73.5% 66.7%

[0082] It can be seen from Table 3 that the pellet binder provided by the present invention can significantly improve the one-time forming rate of phosphate tailings.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A pellet binder, characterized in that: The preparation includes the following raw materials by weight: 40-60 parts of zinc carboxyl complex slurry, 20-30 parts of inorganic gel particles, 10-20 parts of amphoteric metal compounds, and 5-15 parts of modified montmorillonite; The raw materials for preparing the zinc-containing carboxyl complex slurry include: 20 parts of carboxymethyl cellulose ester, 10 parts of sodium polyacrylate, 5 parts of sodium lignin sulfonate, 1 part of coupling agent, 1 part of sodium hydroxide, 20 parts of water and 3 parts of zinc compound; The inorganic gel particles are one or more of calcium oxide, cement, high modulus sodium silicate, magnesium chloride, alum and hydrotalcite.

2. The pellet binder according to claim 1, characterized in that The preparation method of the zinc-containing carboxyl complex slurry comprises: Mixing carboxymethyl cellulose ester, sodium polyacrylate, sodium lignin sulfonate and a coupling agent to obtain a mixed powder; After dissolving sodium hydroxide in water, the obtained sodium hydroxide solution, mixed powder and zinc compound are mixed to obtain zinc-containing carboxyl complex slurry.

3. The pellet binder according to claim 1, characterized in that: The carboxymethyl cellulose ester is one or more of carboxymethyl cellulose acetate propionate, carboxymethyl cellulose acetate butyrate and carboxymethyl cellulose stearate.

4. The pellet binder according to claim 1, characterized in that The coupling agent is one or more of KH550, KH560, KH570, tetrabutyl titanate, isopropyl trititanate and aluminate coupling agent.

5. The pellet binder according to claim 1, characterized in that: The zinc compound is one or more of zinc oxide, zinc chloride, zinc sulfate, zinc acetate and zinc hydroxide.

6. The pellet binder according to claim 1, characterized in that: The amphoteric metal compound is one or more of aluminum oxide, aluminum hydroxide, iron oxide and cobalt oxide.

7. The pellet binder according to claim 1, characterized in that: The modified montmorillonite is sodium-based montmorillonite and / or cellulose ether-modified montmorillonite.

8. The method for preparing the pellet binder according to any one of claims 1 to 7, characterized in that: The following steps are involved: The zinc-containing carboxyl complex slurry, inorganic gel particles, amphoteric metal compounds and modified montmorillonite are mixed, and then dried and ground in sequence to obtain a pellet binder.

9. Use of the pellet binder according to any one of claims 1 to 7 or the pellet binder prepared by the preparation method according to claim 8 in phosphate tailings powder.

Citation Information

Patent Citations

  • Binder for ore pelletizing, processes for the production of ore pellets, use of a flux, and use of a binder.

    BR102017019748A2

  • Environment-friendly antibacterial glue

    CN105950072A